Gender and production: toward an cconomic history attuned to structural inequalities (Ágora Journal, 2025)
This article reflects on the incorporation of gender studies into the field of Economic History as an epistemological shift, not merely a thematic expansion. It argues that traditional economic historiography has neglected the role of gender relations in shaping productive and distributive systems, reinforcing an apparent analytical neutrality. The proposal combines feminist critiques of political economy with the historiographical renewal of the Annales school, especially regarding long-term structures and social foundations. Authors such as Joan Scott, Silvia Federici, and Maria Mies are referenced to demonstrate how gender, class, and racial hierarchies shape economic dynamics. Drawing on examples from women's labor history in Brazil, the slave-based economy, and contemporary domestic economies, the article advocates for expanding the concept of “economic production” to include reproductive labor, care work, and informality. In doing so, it seeks to critically renew Economic History, making it more responsive to social change and aligned with contemporary debates on justice and recognition.
Keywords: Economic History; Gender; Labor; Feminist Economics; Social Reproduction